Clinical Efficiency of Absorbing Wound Dressing Consisting of Nanostructured Graphite in Comparison with Other Modern Dressings; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Shteynle А. V. Aleksandr Vladimirovich (2012, 2012)
Title screen